Clinicopathological study of salivary gland tumors: an assessment of 303 patients - Maria de Lourdes Silva de Arruda Morais; Paulo Roberto Azevedo; Cyntia Helena Carvalho; Lélia Medeiros; Tirzah Lajus; Antonio de Lisboa Lopes Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
Salivary gland neoplasms are remarkable for their histological diversity and several studies point to their varied occurrence in the population. Clinical aspects were histologically assessed to determine possible associations and define parameters to differentiate benign and malignant neoplasms. The case files of patients diagnosed with epithelial salivary gland tumors between 1989 and 2005 were reviewed. A majority (71%) of the 303 salivary gland tumors studied were benign and pleomorphic adenoma were found to be most common. Mean ages for patients with benign and malignant tumors were 49.2 and 58.5 years, respectively. A statistically significant difference between these tumors was observed for the following variables: mean age, tumor size and disease duration. A correlation was found between histological diagnosis and tumor consistency. The data presented here corroborate a number of previous studies and are therefore relevant in understanding the diverse characteristics exhibited by these tumors.